Підсумки інтродукції деревних декоративних рослин у приозерно-балковий ландшафтний район дендропарку “Тростянець” - Medvedev, V.A.; Iljenko, O.O. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2013)
The dynamics of strange arboreal plants in lakeside-gully area of dendropark Trostjanets is investigated. It is presented a numerical score of their viability on the genesic development indexes, winter resistance and drought-resistingness. The estimation of success of introduction of 140 species and cultivars of arboreal plants in lakeside-gully area of denropark is given.